Penguatan Efikasi Diri Menyusui Ibu Bekerja Melalui Edukasi Berbasis Media Informasi - Irianti, Dewi; Pusparina, Iis; Ikasari, Filia Sofiani (Idea Pengabdian Masyarakat, 2024)
The lowest coverage of exclusive breastfeeding was in Kalimantan (37.5%). The target of exclusive breastfeeding in Banjar district was only 28.73% achieved. The results of research that has been conducted on the relationship between breastfeeding self-efficacy for working mothers and exclusive breastfeeding, the results state that psychological conditions are the factor most related to exclusive breastfeeding. The purpose of this community service activity is to strengthen the knowledge of mothers in Cahaya PAUD about “Strengthening Breastfeeding Self-Efficacy for Working Mothers”. The educational method used is the two way method, namely question and answer using leaflet media. This media makes it easier for mothers to discuss with the service team while education is given. This activity provides reinforcement to the mother that psychological conditions will be related to exclusive breastfeeding